Mini Review of Phytochemicals and Plant Taxa with Activity as Microbial Biofilm and Quorum Sensing Inhibitors - Ta, Chieu; Arnason, John (Molecules (Basel, Switzerland), 2015)
Microbial biofilms readily form on many surfaces in nature including plant surfaces. In order to coordinate the formation of these biofilms, microorganisms use a cell-to-cell communication system called quorum sensing (QS). As formation of biofilms on vascular plants may not be advantageous to the hosts, plants have developed inhibitors to interfere with these processes. In this mini review, research papers published on plant-derived molecules that have microbial biofilm or quorum sensing inhibition are reviewed with the objectives of determining the biosynthetic classes of active compounds, their biological activity in assays, and their families of occurrence and range. The main findings are the identification of plant phenolics, including benzoates, phenyl propanoids, stilbenes, flavonoids, gallotannins, proanthocyanidins and coumarins as important inhibitors with both activities. Some terpenes including monoterpenes, sesquiterpenes, diterpenes and triterpenes also have anti-QS and anti-biofilm activities. Relatively few alkaloids were reported. Quinones and organosulfur compounds, especially from garlic, were also active. A common feature is the polar nature of these compounds. Phytochemicals with these activities are widespread in Angiosperms in temperate and tropical regions, but gymnosperms, bryophytes and pteridophytes were not represented.